Dielectric properties of a wide-temperature ferroelectric phase in a fluorinated compound. (3rd August 2017) - Perkowski, P.; Żurowska, M.
ABSTRACT: A broad-frequency dielectric spectroscopy (100 Hz to 10 MHz) was used to investigate newly synthesized fluorinated compound. This compound exhibits a wide-temperature ferroelectric phase. Due to the fact that the compound does not crystallize at temperatures available in our DSC equipment, additional measurements were done at the very low temperatures (down to −100 °C) to find the crystallization temperature. Finally, we did not manage to crystallize the investigated compound. Compound under studies seems to be overcooled. Observed dielectric modes are described and their parameters are shown in this paper. Additionally, DC field influence on dielectric response is shown and analyzed here. Both modes observed at the low temperature are recognized as the molecular ones.